Tissue Kallikrein Preventing the Restenosis after Stenting of Symptomatic MCA Atherosclerotic Stenosis (KPRASS). Issue 4 (June 2014) - Lan, Wenya; Yang, Fang; Liu, Ling; Yin, Qin; Li, Min; Li, Zhuangli; Sang, Hongfei; Xu, Gelin; Ma, Minmin; Zhang, Zhizhong; Liu, Zhenguo; Liu, Xinfeng; et al.
Rationale: Many recent studies suggest that the kallikrein-kinin system play a protective role in the impairment of vascular smooth muscle cells and vascular endothelial cell. Aims: The study aims to determine whether tissue kallikrein is efficacy for preventing the long-term in-stent restenosis after stenting of symptomatic atherosclerotic stenosis of the middle cerebral artery M1 segment. Design: This is a Phase II, randomized, single-blinded, controlled trial. In line with SAMMPRIS stenting indications, patients ( n = 90) with the symptomatic the middle cerebral artery M1 segment stenosis ⩾70% and successfully treated with stent will be enrolled. Eligible patients will be randomized using computer generated numbers, and allocated to receive tissue kallikrein treatment or not. Patients in tissue kallikrein treatment group will be prescribed with intravenous infusion of tissue kallikrein (0·15 PNAU/d, dissolved in 100 ml saline) for 7 days after stenting and then oral administration of pancreatic kallikrein enteric-coated tablet (240 U, 3/d) to the end of study. As the foundation treatment, all the enrolled patients will receive aspirin (100 mg/d), clopidogrel (75 mg/d), and atorvastatin (20 mg/d) for the first 6 months and continue with the combination of aspirin and atorvastatin at the previous dosage. Study outcomes: Patients will be evaluated at 1, 6 and 12 months after stenting. The primary outcomes are the in-stent restenosis rate, new stroke or aggravation of the previous ischemic stroke ipsilateral to the severe stenotic artery. Secondary outcomes include stroke of other artery territories, myocardial infarction and vascular death. Modification of stroke knowledge, exercise and diet habit, smoking cessation and available laboratory data will also be recorded. Conclusion: As our pilot study, tissue kallikrein would be expected to prevent the long-term in-stent restenosis after stenting of the symptomatic middle cerebral artery dramatically.